A review of photovoltaic/thermal (PV/T) technology applied in building environment control - Xuhui Cao; Niansi Li; Yulin Li; Lei Che; Bendong Yu; Huifang Liu (Energy and Built Environment)
Solar energy is widely used to replace traditional energy because of its clean and efficient characteristics. Solar energy has great application potential and prospects in building energy conservation. Combining solar energy with buildings can achieve higher efficiency while reducing costs, and the life of the system is longer. PV/T technology combines solar photovoltaic and photothermal technology and obtains sustainable electrical energy and thermal energy at the same time. PV/T systems can be easily integrated to buildings and the electricity and heat generated by PV/T can drive a variety of physical and chemical processes such as heat collection process, solid/liquid dehumidification process and photo/thermal catalytic purification process. Therefore, building-integrated PV/T system has good application potential in building environment control such as indoor air temperature, air humidity and gaseous pollutants control. In the review of the past decade at home and abroad, most of the research on PV/T focuses on the development process, equipment and materials, accounting for 28 %, 21 % and 19 %, respectively, while only 15 % is related to the building-integrated PV/T system. The present work mainly investigates the application of PV/T in building environment in the past ten years, and reports a variety of application cases of PV/T technology combined with building systems to regulate indoor comfort and improve indoor environment. In addition, this paper reviews the simulation and experimental works of different building solar integrated PV/T systems and puts forward the prospect and suggestion for future research.